Shaping ability of three nickel-titanium rotary instruments in simulated L-shaped canals: OneShape, Hero Shaper, and Revo-S - Pouyan Vakili-Gilani; Saeid Tavanafar; Abdul Rahman Mohammad Saleh; Hamideh Karimpour (BMC, 2021)
Abstract Background Shaping ability of a file plays an important role during instrumentation in an endodontic treatment. This study aimed to compare the shaping ability of OneShape (OS), Hero Shaper (HS), and Revo-S (RS) instruments in simulated L-shaped canals. Methods Forty-eight simulated L-shaped canals were prepared to an apical size of 25 using OS, HS, and RS (all from Micro-Mega SA, Besançon, France), (n = 16 canals/group) systems. The amount of resin removed after each canal's preparation was measured and compared after producing a composite image made from the superimposition of pre and post-instrumented canals. Canal aberrations and the preparation time were also recorded. The data were statistically analysed by using ANOVA, Tukey, and Chi-square tests. Results One file fractured during instrumentation in the RS group. A significant difference was found at the apical end of the prepared simulated canal between the groups, with RS showing the least amount of resin removal from the inner side of the canals and HS showing the highest amount of resin removal from the outer side (P < 0.05). Regarding the total width of the canals after preparation, a significant difference was found between the groups at the apical end and the straight portion of the canals, and RS removed the least amount of resin at the straight portion of the canals (P < 0.05). No statistically significant differences were found between the different instruments regarding canal aberrations' incidence (P > 0.05). Conclusions All of the files showed a tendency to straighten the canals, whereas OS files maintained the original canal curvatures well.